PENINGKATAN KETERAMPILAN GERAK DASAR ROLL BELAKANG PADA ANAK SEKOLAH DASAR - Farhan Ramadhani Pangkey; Imam Mahfud (Universitas Teknokrat Indonesia, 2020)
The purpose of this study was to determine the improvement of basic skills back roll using aids in class III students of SD N 1 Beringin Raya Bandar Lampung city in 2019. The method used in this research is the Classroom Action Research method with two cycles , where in each cycle using different actions. The first cycle with the use of part-time learning, and the second cycle with the use of teacher assistance.The subjects in this study were students III of SDN 1 Beringin Raya, Bandar Lampung City, totaling 17 students. Data collection was taken from tests in the form of observations of the basic roll rear motion skills which include initial attitude, implementation and final attitude. The results of this study indicate an increase in basic roll rear motion skills through the use of assistive devices in each cycle, while the increase in each cycle is as follows the first cycle of 52.94%, and the second cycle 82.35%Keywords: Enhancement, Skills, Basic Movement, Gymnastics, Back Roll